Kualitas Pelayanan Publik di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Mamberamo Tengah - Oktavianus Randa Lembang; Abner Herry Bajari; Ari Juliana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze public services in Central Mamberamo Regency with a focus on licensing and non-licensing services implemented by the Investment and One-Stop Integrated Service Office. To conduct an in-depth analysis, the method used is descriptive qualitative. Direct observation to the research location, interviews using question guidelines, and conducting studies of various documents related to the research topic are a series of data collection techniques that are classified into two types of data, namely primary data and secondary data. All completed data collection processes are continued with data analysis in three stages. Starting from sorting the results of the data that has been obtained into important parts according to the focus of the research. Second, describing the field findings in narrative form into the discussion. And finally analyzing the results of the data presentation in a conclusion related to licensing and non-licensing services. The results of this study found that facilities, low service room support capacity, and the time to complete licensing applications did not support the licensing and non-licensing service process so that the quality of service was not yet qualified. Coupled with low employee discipline, inadequate number of officers, and minimal training for service officers are factors that fall into the category of service systems and officer capabilities that affect licensing and non-licensing services in Central Mamberamo Regency. Keywords: Quality of Licensing Services, Central Mamberamo